PENGARUH PENGEMBANGAN INOVASI PENELITIAN TERHADAP KEMAMPUAN MENELITI GURU SMA DI KECAMATAN LAGUBOTI SUMATERA UTARA - Zandroto, Weni Ayu Sunita; Purba, Sukarman; Lubis, Wildansyah (Dharmas Education Journal (DE_Journal), 2024)
This research aims to investigate the impact of developing research innovations initiated by schools and/or local governments on increasing the research abilities of high school teachers in Laguboti District. The main focus of the research is to analyze the extent to which innovative initiatives in research supported by schools or local governments contribute to improving the research capabilities of teachers in the region. The research method used included collecting primary data through questionnaires distributed to high school teachers in Laguboti District. Secondary data is also taken from documentation of research innovation development initiatives implemented by schools or local governments. Data analysis was carried out using descriptive statistics and simple correlation, which measures the extent to which the role of the school/government influences teachers' research abilities. It is hoped that the research results will provide a clear picture of the effectiveness of developing research innovations by schools and/or local governments in improving the research capabilities of high school teachers in Laguboti District. It is hoped that the implications of this research finding can become the basis for improving educational policies and practices in the region.